Respuesta :

Answer:

f^-1(x) = (x - 2)/4 ⇒ 1st answer

Step-by-step explanation:

* Lets revise how to find the inverse function

- At first write the function as y = f(x)

- Then switch x and y

- Then solve for y

- The domain of f(x) will be the range of f^-1(x)

- The range of f(x) will be the domain of f^-1(x)

* Now lets solve the problem

∵ f(x) = 4x + 2

∴ y = 4x + 2 ⇒ switch x and y

∴ x = 4y + 2 ⇒ subtract 2 from both sides

∴ x - 2 = 4y ⇒ ÷ 4 both sides

∴ (x - 2)/4 = y

∴ f^-1(x) = (x - 2)/4

* f^-1(x) = (x - 2)/4